Ilmu pengetahuan dan cara berpikir Auguste Comte dan Van Peursen - Nadhiroh, Elvinatun (Maliki Interdisciplinary Journal, 2025)
Science develops alongside changes in the way humans think about and understand the world. Auguste Comte and D.H.Th. Van Peursen are two prominent figures who explain this development through their respective conceptual frameworks. This study aims to compare their approaches to thinking and examine their influence on the understanding of science. The method used is a literature review with a descriptive qualitative approach. Comte divides the stages of human thought into theological, metaphysical, and positive phases, emphasizing scientific observation and verification as the foundation of science. In contrast, Van Peursen proposed three stages of thinking—mythical, ontological, and functional—which highlight the roles of meaning, culture, and social function. This comparison shows that Comte’s approach is more systematic and objective, while Van Peursen’s is more flexible and contextual. In conclusion, a comprehensive understanding of science requires integrating both perspectives, so that science is not only methodologically rigorous but also socially and culturally relevant.